Towards Social Justice in the Neoliberal Bologna Process - Kushnir, Iryna; Eta, Elizabeth Agbor (Emerald Publishing, 2023)
Towards Social Justice in the Neoliberal Bologna Processis essential reading for higher education scholars, policymakers, and postgraduate students across the EHEA, as well as countries beyond the EHEA that have been aligning their systems of education to the Bologna Process.